Sumo - Romero, Pablo; Moro, Luis Sebastián (Base Diseño e Innovación, 2019)
Company dedicated to the design of spaces and specializes in museography. SUMO conceives, designs and produces exhibition spaces, for museums, cultural centers and private and public institutions. Our projects have an immersive and evocative hallmark, and seek to generate an emotional and meaningful experience for the public.